Preparation and Characterization (Mechanical and Water Absorption Properties) of CMC/PVA/Clay Nanocomposite Films - Behjat Tajeddin; Najmeh Ramedani (Iranian Journal of Chemistry & Chemical Engineering, 2016)
The aim of this study was to produce Carboxy Methyl Cellulose (CMC) and Poly Vinyl Alcohol (PVA) films and to enhance their properties by reinforcing them with nanoclay particles. Thus, nanocomposite films were prepared with blending of CMC and PVA, as a matrix and several filler loadings of nanoclay particles. The various formulations of nanocomposite films obtained with casting method and their different characterizations were studied. The mechanical and water absorption properties of these films are discussed in this article. Results showed that with increasing filler loading, Tensile Stress (TS), elongation at break (E), and Modulus Of Elasticity (MOE) of the CMC/PVA/nanoclay composites raised, decreased, and enhanced, respectively. In addition, water absorption of films decreased asmore filler was incorporated in the composite. X-Ray Diffraction (XRD) patterns showed that films containing 3% clay have proper mixing and exhibited the best dispersion in the CMC/PVA matrix.